Quality of Arguments Used in the First-Round Presidential Debate: Critical Pragmatics and Stephen Toulmin’s Perspective - Setyaningsih, Yuliana; R. , Kunjana Rahardi (International Journal of Psychosocial Rehabilitation, 2020)
It is important for politicians to have good argumentative skills. For state leaders, the ability to think logically, to use rhetoric, and to argue systematically, scientifically, sharply, and eloquently is very crucial. The year 2019 is the political year for Indonesia. Political campaigns leading to the presidential and legislative elections, both at national and regional levels, will happen in 2019. The focus of this research is to investigate the depth and breadth of the arguments stated by the presidential candidates and how those arguments are presented. The substantial research data source is in the form of a speech transcript of the recorded video of the first-round presidential debate by two pairs of president and vice president candidates. The research data were the debate arguments found in the video transcript and the contexts surrounding them. The data gathering method used observation by employing recording and note-taking techniques. After the data were gathered, they were selected and classified based on their types for further analysis. The analysis method was the distributional method and content analysis. Both data analysis methods were applied to yield significant results of the study. The results showed that there are simple patterns of argument containing claim, subclaim, data, and warrant. The orders of elements of arguments might be varied. The research results also showed that there were various pragmatic meanings found in the arguments used by the president and vice president candidates. The results of the study, which was analyzed using the critical pragmatic perspective, reflect how far the candidates were concerned with the marginalized, the underprivileged, and the subjugated people.